Sustained effects of porcine somatotropin administered during the growing period on growth and carcass characteristics of finishing pigs - G E Fitzner; Donald H Kropf; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1992)
Forty six barrows were fed a common diet after completing a 35 d growth trial in which 50% received 5 mg/d of pST and the other 50% a placebo injection. At the conclusion of the growing trial (130 lb), the pST-injected pigs were leaner (22%) and yielded carcasses with larger longissimus muscle area (21 %). However, pigs fed to a slaughter weight of 225 lb yielded carcasses that were not different from control pigs in length, longissimus muscle area, or belly weights. Pigs administered pST during the growing phase continued to have 10% less backfat, which resulted in a 1.6% greater yield of lean cuts. Postinjection growth rate of pST-treated pigs was significantly reduced for the initial 2 wk to cause an overall reduced ADG during the finishing period. Days to reach slaughter did not differ with treatment because those pigs previously receiving pST were heavier initially. There is no advantage to injecting pigs with pST during the growing phase to improve overall growth. However, pST administration during the growing phase appears to have a sustained effect on carcass fat thickness of pigs slaughtered at 225 lb.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; G-F; Performance; Carcass; Repartition